Research on the Deformation Law of Jointed Surrounding Rock during Tunnel Excavation Based on Hydromechanical Coupling - Yan Wang; Mingfei Li (Geofluids)
The coupling of the joint network and groundwater in rock under bias conditions has a significant impact on the deformation and failure of the surrounding rock due to tunnel excavation. This paper studies the deformation and failure of surrounding rock after tunnel excavation under different joint network and groundwater conditions. A finite element-based composite joint network modeling method is proposed in this paper, and the typical parameters of the surrounding rock, such as the plastic zone size, vertical displacement, and lateral displacement, are analyzed and compared through numerical calculations. According to the different stratum and hydraulic conditions considered, four numerical models under four different working conditions are established and studied. The deformation and failure laws of the surrounding rock during tunnel excavation are obtained. The results show that with a single joint network, when there is no influence of groundwater, the surrounding rock mainly undergoes shear failure at the arch crown after tunnel excavation. When the influence of groundwater is considered, there are differences in the mode of damage between the left and right sides of the tunnel. The stratum approximately 1 m from the invert breaks, and the right sidewall fails approximately 1 m from the measuring point. In rock with a composite joint network, when groundwater is not considered, two kinds of failures occur in the surrounding rock near the tunnel; however, the surrounding rock far from the tunnel is dominated by shear failure. The stratum approximately 3.5 m from the arch crown fractures and the surrounding rock within approximately 5.5 m from the measurement point on the right sidewall undergoes separation failure. Under the dual effects of joints and groundwater, soft rock deforms considerably. The total hydraulic gradient decreases from left to right before and after tunnel excavation. The total hydraulic gradient of the composite joint network strata is generally smaller than that of the single joint network. In the composite joint network strata, the total hydraulic gradient near the tunnel changes dramatically. This research can provide a reference for tunnel engineering under similar conditions.